2017
DOI: 10.1167/iovs.17-22804
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Haplogroups Modify the Effect of Diabetes Duration and HbA1c on Proliferative Diabetic Retinopathy Risk in Patients With Type 2 Diabetes

Abstract: PurposeWe previously demonstrated an association between European mitochondrial haplogroups and proliferative diabetic retinopathy (PDR). The purpose of this study was to determine how the relationship between these haplogroups and both diabetes duration and hyperglycemia, two major risk factors for diabetic retinopathy (DR), affect PDR prevalence.MethodsOur population consisted of patients with type 2 diabetes with (n = 377) and without (n = 480) DR. A Kruskal-Wallis test was used to compare diabetes duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, for patients with haplogroup UK, neither diabetes duration nor HbA1c level was a significant risk factor for PDR. 73 A larger more recent study looking at the same haplotypes failed to show that association. 74 Another genetic study evaluated patients with type 2 diabetes who were carriers of the HMGA1 rs139876191 variant.…”
Section: P71mentioning
confidence: 96%
“…However, for patients with haplogroup UK, neither diabetes duration nor HbA1c level was a significant risk factor for PDR. 73 A larger more recent study looking at the same haplotypes failed to show that association. 74 Another genetic study evaluated patients with type 2 diabetes who were carriers of the HMGA1 rs139876191 variant.…”
Section: P71mentioning
confidence: 96%
“…Using the same cohort, Mitchell et al . found duration of diabetes and HbA1c was significantly associated with PDR in haplogroups H1 and H2, but not UK, suggesting that mitochondrial haplogroups modify these clinical risk factors for the development of PDR in type 2 diabetes 18 . In a different study, Kofler et al .…”
Section: Discussionmentioning
confidence: 89%
“…While mtDNA variants can contribute to disease in humans ( Taylor and Turnbull, 2005 ; Tuppen et al, 2010 ) and mtDNA haplogroups have been reported to associate with various disorders including psychiatric ( Magri et al, 2007 ; Kazuno et al, 2009 ; Rollins et al, 2009 ), cardiovascular ( Benn et al, 2008 ; Veronese et al, 2019 ), and metabolic diseases ( Chinnery et al, 2007 ; Tavira et al, 2014 ; Mitchell et al, 2017 ; Zhao et al, 2019 ), these studies fail to encompass the complexity surrounding mitonuclear epistasis and environment interactions ( Mossman et al, 2016a ). Mitonuclear genetic variation embodies extraordinarily complex epistatic, pleiotropic and GxE interactions that function in non-additive ways to modify organismal fitness and survival.…”
Section: Discussionmentioning
confidence: 99%